Market share analysis and market segmentation of android-based mobile phone products in sibolga city: market share - Hutabarat, Indra Setiawan; Hutabarat, Sinta Veronika; Panggabean, Yusi Tri Utari; Hanum, Rahmadiah (Institute of Computer Science (IOCS), 2024)
This study aims to find out how big the smartphone market share is and see which type of smartphone dominates the market and becomes the Top Leader, as well as see the most promising market segmentation, the research method is used by market estimate analysis and the distribution of questionnaires to 50 respondents, from the results of the research it was found that Oppo SmartPhone has occupied the top position of the smartphone market with an annual sales achievement of 8,395 data taken from Mobile phone counters in the Sibolga City area, North Sumatra Province